(untitled) (Global Journal of Management and Business Research, 2013)
A nation’s financial system is much more than just an intermediary that ensures the allocation of savings to investment. The efficiency of such a system is endogenously achieved if the financial structure of that economy promotes optimal use of the resources available for development. It is against the importance of finance in enhancing economic growth and development especially in developing economies like Nigeria, that we questioned whether financial structure has positive and significant impact on economic growth and development in Nigeria. The results revealed from our findings support existing literature that total financial structure has positive and significant impact on economic growth. However, while some sectors exert more influence (banking and market), other sectors (such as insurance) were found to have non-significant impact on economic growth. We therefore recommend that greater efforts should be made by govern-ment and the regulatory authorities at ensuring that an enabling environment is provided (through strengthening of existing laws and regulations) where all the components of the financial sector can compete favorably.